The Influence of Statistical Literacy and Critical Thinking Skills on Student Learning Outcomes in Statistics Material - Ahmad Choirul Anam (Jurnal Multidisiplin Ibrahimy, 2026)
This study aims to determine the effect of statistical literacy and critical thinking skills on student learning outcomes in statistics material at SMAN Purwoharjo, Banyuwangi. The study used a quantitative correlational approach with 36 students of grade X in the even semester as subjects. Data were collected through statistical literacy tests, critical thinking skills assessment instruments, and statistical material learning outcome tests. Data analysis was conducted using multiple linear regression. The results showed that statistical literacy and critical thinking skills had a positive and significant effect on student learning outcomes, both partially and simultaneously. The coefficient of determination value of R² was 0,72 indicates that 72% of the variation in student learning outcomes can be explained by statistical literacy and critical thinking skills. Partially, critical thinking skills have a greater contribution, namely β = 0,471, compared to statistical literacy with β = 0,401. These findings indicate that statistical learning outcomes are not only influenced by calculation skills, but also by the ability to understand data, interpret statistical information, evaluate arguments, and draw logical conclusions.